Assessing Fiscal Space for Health in Nepal - Belay, Tekabe (World Bank Group, Washington, DC, 2015)
Nepal has seen impressive improvements in health outcomes and has done well both in its rate of progress and relative to its income level. Infant mortality has been declining over the past five decades to 38.6 per 1,000 live births in 2009. Similarly, maternal mortality has decreased to 380 per 100,000 live births in 2008. Life expectancy has been steadily increasing to 67 years in 2009. The rate of progress is better than those witnessed by neighboring countries. But challenges remain in addressing inequality, high and increasing out of pocket payments. Geographic and income-related inequalities in population health outcomes remain large and are increasing. For example, not only is the decline in infant mortality not uniform, some regions have seen an increase. The policy response to these challenges has been to expand free care services and pilot protection mechanism against the financial risk of ill health. There is growing demand to expand the package as well as the coverage of existing free essential health care to all Nepalese; to introduce new programs such as health insurance, and other similar initiatives This note identifies efficiency gains as the main potential source of additional fiscal space. The analysis presented herein indicates that improvement in health system efficiency i.e., getting more value for money is by far the most plausible option for realizing additional fiscal space for health in Nepal. As the note demonstrates, the prospects for additional resources for health from all other possible sources from conducive macroeconomic conditions, re-prioritization of health, external resources, and other health-sector specific sources is limited in Nepal. On the other hand, there are many indications of systemic inefficiencies in the health system of the country and the challenge would be to focus on identifying and implementing appropriate interventions to improve the situation and reduce waste. The note highlights some specific areas, such as those related to provider payments, drug procurement mechanisms, and hospital and district grant allocations whereby significant improvements in obtaining better value for money can be realized.